Manipulação de imagens astronômicas com o uso Aladin para o ensino de astronomia - Lima, Melina Silva de (2015)
We have used the Aladin software, a sky atlas used to visualize and manipulate astronomical images developed by CDS of Strasbourg. To elaborate teaching activities involving astronomical concepts, such as distance, brightness, image manipulation, colors as well as to explain the nature of different objects showing their images in different filters, among others. In the total, we have elaborated four activities that were applied to students of the 6th year of elementary school, high school and undergraduate ones for the Engineering and Pedagogy courses. All activities and the results of their evaluation with students are detailed discussed and analyzed; a teacher guide is also provided. Our results show that in the four activities, the students have a significant learning supporting the use of such methodology. Also, we elaborated two memory games, based on Java platform, with the images of some astronomical objects. The activities are in The Portuguese language, but they can easily be adapted for any other language. This research also made the translation of Aladin to Portuguese.